THE CHALLENGE OF EDUCATING ON THE CHARACTER OF STUDENTS IN FACING THE SOCIETY ERA 5.0 - Vivin Devi Prahesti; Sedya Santosa (Fenomena, 2022)
The study aims to study the challenge of educating children about characteristics in Islamic Elementary schools dealing with society 5.0. Children of Islamic Elementary Schools are prepared to deal with the challenge experienced in the next future in various ways.  The study is conducted in MI Bilingual Roudlotul Jannah. The study uses observation and documentation techniques to know the strategies and rapprochement that educators use to teach children characteristics. The data analysis is operated by using Miles and Huberman techniques through data reduction based on data. The finding is that educators implement HOTS assessment and collaboration between parents and educators. The result of the study is that educators prepare students to deal with society 5.0 so that characteristic education for children does not affect globally. Those children implement Islamic education based on Islamic education that is insan kamil through the vision and mission Islamic religion.